CPC-095 Off-Label Use of Anakinra in a Patient with Familial Mediterranean Fever: A Case Report. (12th March 2013) - Valiente, F; Sánchez, I; Martínez-Blázquez, A; Rodríguez, MA; Ramos, J
Abstract : Background: Familial Mediterranean Fever (FMF) is an autosomal recessive autoinflammatory disease characterised by periodic episodes of fever, peritonitis, arthritis and may be complicated by secondary amyloidosis. FMF affects groups of people from around the Mediterranean Sea. Colchicine is the standard treatment in the prevention of both acute attacks and secondary amyloidosis but there are some resistant patients. Anakinra, an interleukin-1 (IL-1) receptor antagonist indicated for the treatment of the signs and symptoms of rheumatoid arthritis in combination with methotrexate, is also known to affect the severity and the frequency of FMF attacks. Purpose: To describe the progress of a patient with FMF treated with anakinra as IL-1 blocker, and evaluate the efficacy and safety of this treatment Materials and Methods: We describe the case of a 53-year-old colchicine-resistant woman suffering from FMF, who was treated with anakinra between April and September 2012 as second-line treatment, after several episodes of recurrent fever and abdominal pain. In order to evaluate the treatment the patient's clinical history and analytical data (C-reactive protein) were reviewed. Results: Anakinra was started with a daily subcutaneous dose (100 mg) associated with oral corticosteroids (methylprednisolone 8 mg). After the first cycle of treatment, the patient was fine, with no recurrent episodes of fever or abdominal pain. C-reactive protein (CRP) fell from 0.8 to <0.1 mg/dl. There were no injection site reactions. The only noteworthy adverse effect was neutropenia (1.4 × 109/L).Corticosteroids and anakinra doses were reduced to zero and 100 mg every other day respectively. Conclusions: In this case of FMF, anakinra successfully suppressed the number of attacks and the symptoms, without significant adverse reactions and with improvement in quality of life. Controlled trials are necessary to confirm the safety and efficacy of interleukin-1 antagonists in FMF patients. No conflict of interest.